Extended effective absorption bandwidth of Sendust/phosphate flaky particles by TiO2 insulation coating. Issue 12 (15th June 2023) - Shen, Fengyuan; Liu, Hongjin; Li, Xinhui; Cheng, Hang; Zhang, Longyan; Liu, Xianguo
Abstract: How to obtain a wide effective absorption bandwidth is still a challenge for Sendust micro-powder as microwave absorber at 2–10 GHz range. Double shell-core structured composites are desirable to extend effective absorption bandwidth through optimizing impedance match degree in wider frequency and forming a broad dielectric loss peak. In this work, TiO2 layer is fabricated on surface of flaky Sendust/phosphate composites through the hydrolysis reaction for constructing double shell-core structured TiO2 @phosphate@Sendust flaky composites. The synergistic effect of TiO2 -phosphate interface and phosphate-Sendust interface induces a broad peak for dielectric loss, microwave absorption ratio and attenuation constant, resulting in wider effective absorption bandwidth of 3.2 GHz compared with that (2.4 GHz) of raw Sendust/phosphate composites. This work offers a facile and effective strategy for extending effective absorption bandwidth of micron-scale microwave absorber.